Time remaining:
Please solve this question. Thanks!

label Mathematics
account_circle Unassigned
schedule 0 Hours
account_balance_wallet $5

Apr 6th, 2015

x = 2y+7 / 9y-5

9xy-5x = 2y+7

9xy-2y = 5x+7

y(9x-2) = 5x+7

y = 5x+7 / 9x-2

therefore, f-1(x) = 5x+7 / 9x-2

Check:

f(f-1(x)) = 2(5x+7/9x-2)+7 / 9(5x+7/9x-2)-5

= 10x+14+63x-14 / 45+63-45x+10

= 73x/73 = x  Therefore it checks out as the inverse

Apr 5th, 2015

Studypool's Notebank makes it easy to buy and sell old notes, study guides, reviews, etc.
Click to visit
The Notebank
...
Apr 6th, 2015
...
Apr 6th, 2015
Jun 24th, 2017
check_circle
Mark as Final Answer
check_circle
Unmark as Final Answer
check_circle
Final Answer

Secure Information

Content will be erased after question is completed.

check_circle
Final Answer